Dupilumab: Clinical Efficacy of Blocking IL-4/IL-13 Signalling in Chronic Rhinosinusitis with Nasal Polyps - Kariyawasam HH; James LK; Gane SB (Dove Medical Press, 2020)
Harsha H Kariyawasam,1– 3 Louisa K James,4 Simon B Gane2,3 1Department of Specialist Allergy and Clinical Immunology, Royal National ENT Hospital, University College London Hospitals NHS Foundation Trust, London, UK; 2Department of Rhinology, Royal National ENT Hospital, University College London Hospitals NHS Foundation Trust, London, UK; 3UCL Ear Institute , University College London, London, UK; 4Blizard Institute, Barts and The London School of Medicine and Dentistry, Queen Mary University of London, London, UKCorrespondence: Harsha H Kariyawasam Email harsha.kariyawasam@nhs.netAbstract: In September 2019, The Lancet published details of two large Phase III double-blind placebo-controlled studies (LIBERTY NP SINUS-24 and LIBERTY NP SINUS-52) confirming the clinical efficacy of the biologic dupilumab in simultaneously blocking both IL-4/IL-13 signalling in chronic rhinosinusitis with nasal polyps (CRSwNP). The studies demonstrated that dupilumab (Dupixent®, Sanofi and Regeneron) 300mg subcutaneously administered was clinically effective when added for patients with moderate to severe CRSwNP already maintained on the standard intranasal steroid mometasone furoate. Duration of treatment ranged from injections either 2 weekly for 24 weeks (SINUS-24) or every 2 weeks for 52 weeks or finally every 2 weeks for 24 weeks stepping down thereafter to every 4 weeks for a further 28 weeks (SINUS-52). Rapid improvements in all important parameters of disease burden were seen with such improvement maintained even where the frequency of injections was decreased. In patients with co-existent asthma, lung function and asthma control scores improved. This is consistent with the one airway hypothesis of shared T2 inflammatory programmes driving both disease syndromes. The studies formed the basis for FDA registration and clinical launch in the US, and EMA approval in Europe. Dupilumab presents a significant new treatment option in an area of urgent unmet therapeutic need in CRSwNP. Should dupilumab prove to be as effective in the real-life clinical environment as it has been in the studies, then a paradigm shift from sinonasal surgery to medical treatment of CRSwNP may need to occur in the ENT community. Questions in relation to best patient selection, combined upper and lower airway therapeutic pathways, long-term safety along with health economics and cost constraints ought now to be addressed.Keywords: inflammation, sinusitis, monoclonal antibody, therapeutics, biologic